Kristologi Feminis: Sebuah Perspektif Eklesiologi Trinitaris - Nyssa Janice (Asosiasi Teolog Indonesia, 2016)
Virtually zero room is afforded in everyday speech, let alone in formal ecclesiastical doctrine, for talk (discourse) concerning the Christ as Female, or even as feminist. This essay considers contingencies concerning a multiplicity of identity regarding the Christ figure, particularly the notion of a womanized Christ. In doing so, this paper aims to minimize the historical contradiction of even having such a conversation, as such pertains to the incarnation of God in the (male) body of Jesus, by first making an appeal to the Creative Christology line of inquiry developed by Muriel Orevillo-Montenegro. Following this initial contingency [concerning Christ], I forward a second contingency [concerning Jesus] by appealing to the perspective of Elizabeth Johnson concerning a multiplicity of identity regarding the prophet of Nazareth, thereby envisaging the womanly face of Jesus. Finally, in order to forward a third contingency [concerning the (social) Trinity], I investigate the notion of a multiplicity of identity regarding the divine Triunity in tandem with the articulation of perichoresis put forth by Miroslav Volf and Catherine Mowry LaCugna. All the while, I interrogate the act of naming God from within a feminist critical frame, thereby drawing upon the linguistic theory of Brian Wren; as well, I engage the constructive ecclesiology of Elisabeth Schüssler-Fiorenza (concerning household of God). This essay thus envisages the relationality within the Triune Godhead by virtue of engaging with a robustly trinitarian ecclesiology serving as portrait for gendered, mutual, interpersonal relationality.